2004
DOI: 10.1292/jvms.66.899
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antimicrobial Agents on the Production and Release of Shiga Toxin by Enterotoxaemic <i>Escherichia coli</i> Isolates from Pigs

Abstract: ABSTRACT. Edema disease (ED) of pigs is an enterotoxaemic disease caused by enterotoxaemic Escherichia coli (ETEEC) infection. Antimicrobial therapy for pigs with ED is controversial because it may induce death of sickish piglets. In this study, we investigated the effects in vitro of 7 antimicrobial agents, ampicillin, gentamicin, colistin, bicozamycin, fosfomycin, sulfamethoxazole-trimethoprim and enrofloxacin, on the release and production of shiga toxin (Stx) 2e by ETEEC strains. We found that more Stx 2e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 15 publications
2
18
0
1
Order By: Relevance
“…However, it was reported [44] that tigecyline reduced stx 2 expression, while another study [19] reported that bicozamycin reduced stx 2 expression, which disagreed with other work [16]. The data in Figure 2 shows that tetracycline had only a weak inductive effect on stx 2 gene expression, which agreed with a previous report [16].…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…However, it was reported [44] that tigecyline reduced stx 2 expression, while another study [19] reported that bicozamycin reduced stx 2 expression, which disagreed with other work [16]. The data in Figure 2 shows that tetracycline had only a weak inductive effect on stx 2 gene expression, which agreed with a previous report [16].…”
Section: Discussionsupporting
confidence: 44%
“…A previous study [16] suggested that they do not induce stx gene expression, whereas another study [20] showed that ceftazidime did not affect stx gene expression whereas panipenem (PAPM) greatly suppressed stx gene expression. Other studies [17, 19] have shown that cefotaxime and meropenem [44] do not affect stx gene expression. By contrast, it was reported [17, 18] that ampicillin increased stx gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of antimicrobials has resulted in the development of antimicrobialresistant STEC on Japanese farms [8,22]. Furthermore, the use of some antimicrobials, such as ampicillin and fosfomycin, is a possible cause for the aggravation of ED symptoms [23]. Accordingly, the use of materials other than antimicrobials is requested for the prevention or treatment of ED, most particularly on farms where antimicrobial-resistant STEC has been identified.…”
mentioning
confidence: 99%
“…1999; Yoh et al. 1999), with the exception of opposite effects in rare examples (one strain in each case: one O139 strain from pig, (Uemura et al. 2004) and one human O157:H7 strain (Grif et al.…”
Section: Discussionmentioning
confidence: 99%